Agricultural Ecology of Irrigation Systems and Sustainable Development in Simalungun region, Indonesia - Damanik, Sarintan Efratani (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this article is to describe the agricultural and environmental problems that are face nowadays, such as agricultural ecology. The problem arises due to changes in the agricultural environment, which makes it no longer adequate to maintain the life of living beings caused by the use of insufficient irrigation water that does not meet the needs. If this is not resolved, it will eventually result in the disruption of the food chain in the ecosystem, which will cause the explosion and destruction of living creatures.